2018
DOI: 10.24014/af.v17i1.5338
|View full text |Cite
|
Sign up to set email alerts
|

Konsep Hikmat Al-Tasyrî’ Sebagai Asas Ekonomi Dan Keuangan Bisnis Islam Menurut Ali Ahmad Al-Jurjawi (1866-1961m) Dalam Kitab Hikmat Al-Tasyrî’ Wa Falsafatuhu

Abstract: Ali Ahmad Al-Jurjawi (1866-1961) a modernist from the Egyptian city of Jarja. Al-Jurjawi lived in a time of shock, known as the Egyptian revolution from the clutches of France. European colonization of the Islamic world (Egypt), which tends to manage the economy with a conventional (secular) system. These conditions affect the construction of scholarship which is occupied by Al-Jurjawi, plus the difficulty of finding the ideal books, especially regarding Islamic law and wisdom or secrets that exist in Islamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…So that the fatwa products can be under the purpose and intent of Allah in setting the sharia law (Sahroini & Karim, 2016;Nasuka, 2017). Likewise, in the scope of sharia business and finance, the existence of maqashid sharia, becomes a means of synergizing between nash and market interests (situation), to ensure that market interests are the actual interests (maslahat), that economic interests are the interests of many communities (benefits), and that business interests are long-term interests according to the maqashid muamalah formulation (business or economy) (Johan, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…So that the fatwa products can be under the purpose and intent of Allah in setting the sharia law (Sahroini & Karim, 2016;Nasuka, 2017). Likewise, in the scope of sharia business and finance, the existence of maqashid sharia, becomes a means of synergizing between nash and market interests (situation), to ensure that market interests are the actual interests (maslahat), that economic interests are the interests of many communities (benefits), and that business interests are long-term interests according to the maqashid muamalah formulation (business or economy) (Johan, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Al-Syatibi, as quoted by Ibn Asyur, also Oni Sahroni, that maqashid sharia is the maslahah or benefit and welfare of humanity both in the world and the hereafter. Meanwhile, according to the scholars of ushul fiqh, defining maqashid sharia with the intended meaning and purpose in presenting law for the benefit of mankind (Sahroini & Karim, 2016;Johan, et al, 2018). Generally speaking, it can be concluded that the maqashid sharia is a concept to understand the intention and purpose of sharia values that implicitly put in the Qur'an and hadith, as God Almighty has set for mankind to achieve world prosperity (happiness) and the hereafter (Mutakin, 2017;Sulaeman, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations